Identification of extended-spectrum beta-lactamase (ESBL) and carbapenemase genes in carbapenemresistant Enterobacteriaceae (CRE) clinical isolates from hospitals in Nan province - Duangkaw, Wirakorn; Khamprom, Naruemon; Tuntrakul, Pitchaya; Deeudom, Manu; Amornthipayawong, Dechphipat; Phannachet, Kulwadee (Biomedical Sciences and Clinical Medicine, 2018)
Objective To identify extended-spectrum beta-lactamase (ESBL) and carbapenemase genes in Escherichia coli and Klebsiella pneumoniae clinical isolates from hospitals in Nan province and to characterize the antibiotic susceptibility of these isolates Methods The antibiotic susceptibility of E. coli and K. pneumoniae against imipenem, meropenem, and ertapenem in specimens collected at Pua Crown Prince Hospital and Nan Hospital between May and September 2016 was determined using Kirby–Bauer disk diffusion and minimum inhibitory concentration (MIC) and the agar dilution method based on Clinical and Laboratory Standards Institute (CLSI) guidelines 2016. Polymerase chain reactions (PCR) were performed to identify the ESBL genes, blaSHV, blaTEM, blaCTX-M-1 group, blaCTX-M-9 group and blaVEB and the carbapenemase genes, blaKPC, blaIMP, blaVIM, blaNDM and blaOXA-48-like. Results Antibiotic susceptibility tests using disk diffusion found that 9 isolates of E. coli and 37 isolates of K. pneumoniae were carbapenem-resistant Enterobacteriaceae (CRE). PCR assays for ESBL gene identification revealed that the most prevalent genes found in E. coli were blaTEM (88.9%) followed by blaCTX-M-1 group (66.7%), whereas K. pneumoniae mainly carried blaSHV (91.9%) and/or blaTEM (89.2%). Carbapenemase-encoding genes detected in both E. coli and K. pneumoniae were blaNDM and blaOXA-48-like. The blaNDM was the most common carbapenemase gene and was always co-harbored with ESBL genes. All isolates that carried blaNDM were resistant to all tested carbapenems (meropenem, imipenem, and ertapenem). Conclusion All CRE isolates from Pua Crown Prince Hospital and Nan Hospital, Northern Thailand harbored ESBL and carbapenemase genes. blaTEM, blaSHV, and blaNDM are the most common beta-lactamase. Some isolates were observed co-carrying more than 3 different types of beta-lactamase genes in each single cell. The finding that ESBL genes were co-harbored with carbapenemase genes in all but 3 CRE isolates suggests that these isolates may have previously contained ESBL genes and developed carbapenem resistance by later obtaining carbapenemase genes. The data from this study provides important information on the epidemiology and the distribution of beta-lactamase genes among Enterobacteriaceae in hospitals in Northern Thailand.